2022
DOI: 10.1073/pnas.2121138119
|View full text |Cite
|
Sign up to set email alerts
|

Highly reversible Zn metal anode enabled by sustainable hydroxyl chemistry

Abstract: Rechargeable Zn metal batteries (RZMBs) may provide a more sustainable and lower-cost alternative to established battery technologies in meeting energy storage applications of the future. However, the most promising electrolytes for RZMBs are generally aqueous and require high concentrations of salt(s) to bring efficiencies toward commercially viable levels and mitigate water-originated parasitic reactions including hydrogen evolution and corrosion. Electrolytes based on nonaqueous solvents are promising for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…It is confirmed that a highly reversible Zn deposition behavior of Zn metal (≥99.0 %) and high anodic stability (∼3.6 V vs. Zn) is achieved in organic electrolytes, e. g., (acetonitrile) AN−Zn(TFSI) 2 , [23] AN−Zn(CF 3 SO 3 ) 2 , [24] DMC‐TMP−Zn(TFSI) 2 (dimethyl carbonate‐trimethyl phosphate) [25] . Recently, Xu et al [26] . have discovered a class of nonaqueous but protic solvent based on the alcohol family.…”
Section: Promising Ways Forwardmentioning
confidence: 99%
“…It is confirmed that a highly reversible Zn deposition behavior of Zn metal (≥99.0 %) and high anodic stability (∼3.6 V vs. Zn) is achieved in organic electrolytes, e. g., (acetonitrile) AN−Zn(TFSI) 2 , [23] AN−Zn(CF 3 SO 3 ) 2 , [24] DMC‐TMP−Zn(TFSI) 2 (dimethyl carbonate‐trimethyl phosphate) [25] . Recently, Xu et al [26] . have discovered a class of nonaqueous but protic solvent based on the alcohol family.…”
Section: Promising Ways Forwardmentioning
confidence: 99%
“…26–29 Although metal anodes such as Al and Mg have low theoretical redox potentials, it is very difficult to realize their highly reversible deposition and dissolution in aqueous electrolytes. 6,30 Moreover, they typically showed high polarization and passivation, which lead to much higher redox potentials than their theoretical values. 18,20 Therefore, it is of great significance to explore new aqueous metal anodes to construct high voltage aqueous metal batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] The continuous outgassing of water during battery cycling or idling not only reduces Coulombic efficiency (CE), but also poses a serious safety concern. It is generally believed that the formation of an SEI layer will inhibit the decomposition of water and may increase the working potential of aqueous batteries, but it is very challenging to realize an AAMB with a voltage as high as 2.42 V. 6,8,30 It was demonstrated that the MnO 2 cathode in MnO 2 /Mn 2+ chemistry with a redox potential of 1.23 V vs. SHE showed excellent electrochemical performance in aqueous electrolytes. [38][39][40] The main problem is therefore focused on the reversibility of plating/stripping reactions of Mn/Mn 2+ on the Mn metal anode in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5a,5b ] On the other hand, the zinc anode parasitic reacts with water and the growth of the zinc dendrite, resulting in the low coulombic efficiency (CE) and continuous electrolyte consumption. [ 2b,6 ]…”
Section: Introductionmentioning
confidence: 99%